2021
DOI: 10.31234/osf.io/3rvgb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The creepy, the bad and the ugly: exploring perceptions of moral character and social desirability in uncanny faces

Abstract: We used implicit and explicit measures to study whether “real” uncanny faces (by faces of Botox users and very ugly people) will be associated with perceptions of bad moral character and social avoidance. Implicit measures showed that uncanny faces were more strongly associated with negative aesthetic evaluations (“ugliness”) than with negative moral evaluation (“moral disgust”). At the explicit level, participants preferred greater social distance from uncanny faces than from neutral faces and inferred that t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Pathological voices are more likely to be categorized as atypical [22,23,24] and are evaluated more negatively across various social dimensions compared to healthy voices [25,26,27,28]. In analogy, previous research has suggested that dysmorphic, diseased, or very unattractive faces are perceived as uncanny or creepy [17,29]. Thus, pathological voices, similarly to dis gured faces, may fall into an uncanny valley as highly realistic yet deviating stimuli.…”
Section: Uncanniness and Deviation From Typical Variationmentioning
confidence: 96%
“…Pathological voices are more likely to be categorized as atypical [22,23,24] and are evaluated more negatively across various social dimensions compared to healthy voices [25,26,27,28]. In analogy, previous research has suggested that dysmorphic, diseased, or very unattractive faces are perceived as uncanny or creepy [17,29]. Thus, pathological voices, similarly to dis gured faces, may fall into an uncanny valley as highly realistic yet deviating stimuli.…”
Section: Uncanniness and Deviation From Typical Variationmentioning
confidence: 96%